Evaluation of the Suitability of Biocompatible Carriers as Artificial Transplants Using Cultured Porcine Corneal Endothelial Cells. (4th March 2019) - Spinozzi, Daniele; Miron, Alina; Bruinsma, Marieke; Dapena, Isabel; Lavy, Itay; Binder, Perry S.; Rafat, Mehrdad; Oellerich, Silke; Melles, Gerrit R.J.
ABSTRACT: Purpose/Aim : Evaluating the suitability of bioengineered collagen sheets and human anterior lens capsules (HALCs) as carriers for cultivated porcine corneal endothelial cells (pCECs) and in vitro assessment of the cell-carrier sheets as tissue-engineered grafts for Descemet membrane endothelial keratoplasty (DMEK). Materials and Methods : pCECs were isolated, cultured up to P2 and seeded onto LinkCell™ bioengineered matrices of 20 µm (LK20) or 100 µm (LK100) thickness, and on HALC. During expansion, pCEC viability and morphology were assessed by light microscopy. ZO-1 and Na + /K + -ATPase expression was investigated by immunohistochemistry. Biomechanical properties of pCEC-carrier constructs were evaluated by simulating DMEK surgery in vitro using an artificial anterior chamber (AC) and a human donor cornea without Descemet membrane (DM). Results : During in vitro expansion, cultured pCECs retained their proliferative capacity, as shown by the positive staining for proliferative marker Ki67, and a high cell viability rate (96 ± 5%). pCECs seeded on all carriers formed a monolayer of hexagonal, tightly packed cells that expressed ZO-1 and Na + /K + -ATPase. During in vitro surgery, pCEC-LK20 and pCEC-LK100 constructs were handled like Descemet stripping endothelial keratoplasty (DSEK) grafts, i.e. folded like a "taco" for insertion because of challenges related to rolling and sticking of the grafts in the injector. pCEC-HALC constructs behaved similar to the DMEK reference model during implantation and unfolding in the artificial AC, showing good adhesion to the bare stroma. Conclusions : In vitro DMEK surgery showed HALC as the most suitable carrier for cultivated pCECs with good intraoperative graft handling. LK20 carrier showed good biocompatibility, but required a DSEK-adapted surgical protocol. Both carriers might be notional candidates for potential future clinical applications.